2019
DOI: 10.1111/os.12458
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Reduction Quality of Femoral Neck Fracture and Femoral Head Necrosis Based on Biomechanics

Abstract: Objective To investigate the biomechanical effects of reduction quality on patients after femoral neck fracture internal fixation. Methods The data of individual patients with femoral neck fractures were reviewed. Data for patients with simple unilateral femoral neck fractures whose reduction quality was evaluated as good by hip X‐ray films after internal fixation were collected from January 2013 to January 2017. The CT data of the patients was used to reconstruct 3D models of the femur and the screw. The spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 25 publications
1
62
0
2
Order By: Relevance
“…As a result, no evidences of deep vein thrombosis and pulmonary embolism were identi ed in this study. Some studies have found that A poor reduction following femoral neck fracture is a risk factor for complications and femoral head necrosis [7]. In our study, all patients achieved a satisfactory reduction by the 1st day postoperatively and there was no signi cant difference between the two groups.…”
Section: Discussionsupporting
confidence: 59%
“…As a result, no evidences of deep vein thrombosis and pulmonary embolism were identi ed in this study. Some studies have found that A poor reduction following femoral neck fracture is a risk factor for complications and femoral head necrosis [7]. In our study, all patients achieved a satisfactory reduction by the 1st day postoperatively and there was no signi cant difference between the two groups.…”
Section: Discussionsupporting
confidence: 59%
“…As a result, micro‐CT was taken into consideration. However, soft tissue cannot be viewed clearly on micro‐CT because it has a high water content 29 . To improve the contrast of biological tissue in micro‐CT imaging, many contrast agents have been used to label the target tissue and to image the microstructure more clearly 30–33 .…”
Section: Discussionmentioning
confidence: 99%
“…Femoral neck fracture is a common type of hip fracture. Due to the special location of the fracture, the incidence of femoral neck fracture necrosis is high, and the prognosis is poor, which seriously affects the patient’s activities of daily life [ 1 ]. For elderly patients, conventional treatment is often used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%